Saurichthys sp. (Greenland) - Argyriou, Thodoris; Giles, Sam; Friedman, Matt; Romano, Carlo; Kogan, Ilja; Sanchez-Villagra, Marcelo (Dryad Digital Repository, 2018)
PLY of all segmented structures in .zip folder